CHONDROBLASTOMA OF THE LUMBAR VERTEBRA - Shakir, Tahir Mehmood; Li, Wenfei; Niu, Chen; Zhang, Ming (Journal of Ayub Medical College Abbottabad, 2018)
Chondroblastoma is an uncommon and benign bone tumour. No more than 10 cases of lumbar chondroblastoma have been reported in the past 20 years. To describe the clinical presentations and radiological features of a rare case of chondroblastoma of the lumbar spine, this study reports one case involving the third lumbar vertebrae. A 22-year-old female presented with left lower back pain and numbness. CT revealed tumour infiltration of the third lumbar vertebrae and left psoas major displacement, which was found to be a chondroblastoma by surgery. Lumbar chondroblastomas are very rare which seem to be aggressive on imaging findings; with soft tissue extension, thin sclerotic rim and bony destruction. When encountering a vertebral lesion that seems to be aggressive on imaging findings, we must be aware of the possibility of chondroblastoma. Keywords: Chondroblastoma; Lumbar Vertebra; CT